Mediações pedagógicas no território de empoderamento popular : uma experiência em processo / Caxias do Sul - RS - Pedro, Joanne Cristina (My University, 2022)
This thesis is constituted as a piece of writing which is interwoven in praxis, in the act of knowing that it is established, methodologically accessing reality. It is inserted in the dialogue with the theoretical field that studies the relations between Popular Social Movements, Work and Education, considering that in the crossing towards the transformation of society, a historical procedure is implied, in which the new is engendered in the concrete, theoretical, and practical struggle, within old relationships. Action research, as a methodological option, is part of the dimension of the militant researcher's social commitment to the participating subjects, turning research, education and social action into methodological moments of a single process, with a view to social transformation. This perspective mobilizes the production of knowledge in connection with the Popular Movement, enabling the subjects involved to collectively construct strategies to face the problems and to overcome the difficulties they come across in everyday life. The objective that is consistent with the mobilizing question of the research corresponds to the analysis of the pedagogical mediation built in the meeting between militants of the Movement of Workers for Rights (MTD) and the community of the Vila Ipê allotment (which is part of the movement), located in Caxias do Sul/RS, in order to systematize the accumulated ruptures as strengths in human and social emancipation, from the peripheral territory. The depicted route corresponds to what we call "crossing the empirical field", in which we identified two methodological moments for the analysis of pedagogical mediation: the immersion of the collective in the stage we named "basic work" (2017 to 2020) and in the stage of "associated work" (2020 to 2022), and both stages intersect and interrelate. We consider the daily life of the peripheral territory, the locus of experience, popular education in its humanizing and emancipatory dimension and the category work as the foundation of the social being, in addition to Socially Necessary Work as the connection between theory and practice. In this composition we are based on the Freire's epistemological framework, also adopting dialectical Historical Materialism as a method of analysis, considering the contributions of Karl Marx, István Mészáros, Edward P. Thompson, Ricardo Antunes, and others. The notion of space, according to Milton Santos, as an accumulation of times, supports us in the analysis of historically constituted and vulnerable peripheries by the interest of capital and dialectically forging spaces of valuing and creation of new rationalities. Participation in the territory is one of the powerful instruments for the construction of Popular Power, in addition to self-organized work. The realization of the soap factory Saboaria Popular Las Margaritas by the group of women of the Movement was a qualitative leap in the organization of organic militancy in the territory, with focus in the concept of associated work, in its ontological dimension, that brings in its bulge, beyond the productive sphere (generation of work and income), a feminist praxis based on Popular Education. The dimension of resistance to oppression/exploitation is expressed in the other fronts of Saboaria: territorial, formative and political, developing in the daily lives of the subjects involved in the experience, as the stage of life and immediate place of their most urgent needs, without losing the connection with the historical totality. This path of Saboaria, which the Systematization of Experiences sought to recover and analyze, reaffirms its construction in a moment permeated by questions: the advent of the pandemic of Covid-19, in which the announcement of the harpening of different crises, among them the structural crisis of capital, mobilizes the action of political solidarity of the working class. Finally, our contribution as a conceptual synthesis, has in the "Pedagogical Flor-ação Process" (Flor-ação in Portuguese is a play on words meaning "flourishing" formed by the words "flower" and "action), its representation, considering elements of Pedagogy of the Oppressed, Socialist Pedagogy and Pedagogy of the Movement, in addition to the Popular and Solidarity Economy as a field of political action based on a society project that advances beyond capital. This process constitutes a living and radical movement, based on practical and real basis, which demands women who graduate in the movement of struggle and contradiction. In this crossing, which has the construction of class consciousness as an horizon, emancipatory potentials and indications of new sociability engendered as real possibilities flourish, and are found in an adverse conjuncture, bringing embryonic forms of Popular Power in their construction. [resumo fornecido pelo autor]
Esta tese se constitui como uma escrita imbricada na práxis, no ato de conhecer que se estabelece, acessando metodologicamente a realidade e se insere no diálogo com o campo teórico que estuda as relações entre Movimentos Sociais Populares, Trabalho e Educação, considerando que na travessia para a transformação da sociedade implica-se uma processualidade histórica, na qual o novo é engendrado na luta concreta, teórica e prática, dentro de velhas relações. A pesquisa-ação, como opção metodológica, se perfaz na dimensão do compromisso social da pesquisadora militante com os sujeitos participantes, convertendo a investigação, a educação e a ação social em momentos metodológicos de um único processo, com vistas à transformação social. Essa perspectiva mobiliza a produção de conhecimento em conexão com o Movimento Popular, possibilitando aos sujeitos envolvidos, construírem coletivamente estratégias de enfrentamento às problemáticas e à superação das problematizações que se apresentam na concretude da vida cotidiana. O objetivo que se coaduna à pergunta mobilizadora da pesquisa corresponde a analisar as mediações pedagógicas construídas no encontro entre militantes do Movimento de Trabalhadoras e Trabalhadores por Direitos (MTD) e a comunidade do loteamento Vila Ipê (que se integra ao movimento), situado em Caxias do Sul/RS, de modo a sistematizar as rupturas acumuladas como potenciais de emancipação humana e social, a partir do território periférico. O percurso retratado corresponde ao que denominamos como "travessia pelo campo empírico", no qual identificamos dois momentos metodológicos para análise das mediações pedagógicas: a imersão do coletivo na etapa que nomeamos "trabalho de base" (2017 a 2020) e na etapa do "trabalho associado" (2020 a 2022), sendo que ambas as etapas se entrecruzam e se inter-relacionam. Consideramos o cotidiano do território periférico, o lócus da experiência, a Educação Popular em sua dimensão humanizadora e emancipadora e a categoria trabalho como fundante do ser social, além do Trabalho Socialmente Necessário como a conexão entre teoria e prática. Nesta composição fundamentamo-nos no referencial epistemológico freiriano, adotando também como método de análise o Materialismo Histórico Dialético, considerando as contribuições de Karl Marx, István Mészáros, Edward P. Thompson, Ricardo Antunes, dentre outros. A noção de espaço, conforme Milton Santos, como acumulação de tempos, nos apoia na análise das periferias, historicamente constituídas e vulnerabilizadas pelo interesse do capital e dialeticamente forjando espaços de valorização e criação de novas racionalidades. A participação no território constitui-se como um dos potentes instrumentos para a construção do Poder Popular, além do trabalho auto-organizado. A concretização da Saboaria Popular Las Margaritas pelo grupo de mulheres do Movimento foi um salto qualitativo na organização da militância orgânica no território, com centralidade na concepção de trabalho associado, em sua dimensão ontológica e que traz no seu bojo, para além da esfera produtiva (geração de trabalho e renda), uma práxis feminista alicerçada na Educação Popular. A dimensão da resistência à opressão/exploração se expressa nas demais frentes da Saboaria: a territorial, a formativa e a política, desenvolvendo-se no cotidiano dos sujeitos implicados na experiência, como palco da vida e lugar imediato de suas necessidades mais urgentes, sem perder a conexão com a totalidade histórica. Esse percurso da Saboaria,que a Sistematização de Experiências buscou recuperar e analisar reafirma a sua construção em um momento permeado por interrogações: o advento da pandemia da Covid-19, no qual o anúncio da agudização de diferentes crises, dentre elas a crise estrutural do capital, mobiliza a ação de solidariedade política da classe trabalhadora. Por fim, nossa contribuição à guisa de uma síntese conceitual, tem no "Processo de Flor(ação) Pedagógica" a sua representação, considerando elementos da Pedagogia do Oprimido, da Pedagogia Socialista e da Pedagogia do Movimento, além da Economia Popular e Solidária como campo de ação política pautado em um projeto de sociedade que avance para além do capital. Tal processo constitui-se como um movimento vivo e radical, com base prática e real, o qual demanda mulheres que se formam no movimento de luta e contradição. Nesta travessia, cujo horizonte é a construção da consciência de classe, florescem potenciais emancipatórios e indícios de novas sociabilidades engendradas como possibilidades reais, gestadas em uma conjuntura adversa, trazendo em sua constituição formas embrionárias de Poder Popular. [resumo fornecido pelo autor]
Keywords: Educação popular - Caxias do Sul (RS); Movimentos sociais; Educação; Popular education - Caxias do Sul (Brazil); Social movements; Education